2019
DOI: 10.3847/1538-4357/ab536f
|View full text |Cite
|
Sign up to set email alerts
|

X-shaped Radio Galaxies: Optical Properties, Large-scale Environment, and Relationship to Radio Structure

Abstract: In order to find clues to the origin of the "winged" or X-shaped radio galaxies (XRGs) we investigate here the parent galaxies of a large sample of 106 XRGs for optical-radio axes alignment, interstellar medium, black hole mass, and large-scale environment. For 41 of the XRGs it was possible to determine the optical major axis and the primary radio axis and the strong tendency for the two axes to be fairly close is confirmed. However, several counter-examples were also found and these could challenge the widel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 87 publications
3
36
0
Order By: Relevance
“…In summary, our 3D relativistic MHD simulations of jet propagation within a tri-axial galactic environment have demonstrated the formation of X-morphology following the Back-flow model as proposed by Capetti et al (2002). One of the observed characteristics of such X-morphology is that in most cases wings coincide with the minor axis of the galaxy (e.g., Saripalli & Subrahmanyan 2009;Gillone et al 2016;Joshi et al 2019). We have performed simulation runs by varying the direction of jet ejection with respect to the major axis of the underlying galaxy and verified such empirical evidence consistent with results obtained by Rossi et al (2017).…”
Section: Jet At An Angle To Major Axissupporting
confidence: 73%
See 1 more Smart Citation
“…In summary, our 3D relativistic MHD simulations of jet propagation within a tri-axial galactic environment have demonstrated the formation of X-morphology following the Back-flow model as proposed by Capetti et al (2002). One of the observed characteristics of such X-morphology is that in most cases wings coincide with the minor axis of the galaxy (e.g., Saripalli & Subrahmanyan 2009;Gillone et al 2016;Joshi et al 2019). We have performed simulation runs by varying the direction of jet ejection with respect to the major axis of the underlying galaxy and verified such empirical evidence consistent with results obtained by Rossi et al (2017).…”
Section: Jet At An Angle To Major Axissupporting
confidence: 73%
“…However, to date, there exists no general agreement between the proposed models to describe the formation process of these galaxies. Also, under which parametric restrictions each of these models work is still not well understood (Joshi et al 2019). Finally, whether there exists any universal model which can explain all the properties of these galaxies or not is also an important question to ask, for these galaxies.…”
Section: Introductionmentioning
confidence: 99%
“…These radio sources are most commonly studied through observations of the kpc to Mpc scale radio lobes (Bennett & Simth 1962;Hardcastle et al 2019b;Seymour et al 2020) inflated by the relativistic jet beam, throughout which a population of relativistic electrons accelerated at shocks emits through synchrotron and inverse-Compton processes Turner et al 2018a) Radio sources have historically been classified into two distinct categories (Fanaroff & Riley 1974) based on whether the large-scale ★ E-mail: patrick.yates@utas.edu.au lobe morphology is edge-darkened (Fanaroff-Riley class I, FR I) or edge-brightened (FR II). As radio telescope sensitivity and resolution have increased, this distinction has become increasingly murky: compact radio sources with some low-frequency extended emission have been termed FR 0s (Garofalo & Singh 2019;Baldi et al 2019;Capetti et al 2019); low luminosity (𝐿 150 ≤ 10 25 W Hz −1 ) FR II radio sources have been observed (Mingo et al 2019); radio sources which exhibit hybrid FR I/II characteristics suggest that precession and projection effects can drastically alter the observed morphology (Harwood et al 2020;Krause et al 2019;Horton et al 2020a,b); the consideration of mergers, cluster weather, and remnant or restarting radio sources further complicates the observed lobe morphology (Mahatma et al 2018;Yates et al 2018;English et al 2019;Joshi et al 2019;Hardcastle et al 2019a;O'Neill et al 2019;Bruni et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have concluded that the morphology and spectral features of some of these sources favor a scenario in which BH spin reorientation occurred on a short timescale ( 10 5 yr; e.g., Cheung, 2007;Mezcua et al, 2011;Gopal-Krishna et al, 2012;Hernández-García et al, 2017;Saripalli and Roberts, 2018). However, other studies find that these X-shaped radio sources are more likely to arise from physics that has nothing to do with MBH spins, such as the backflow of jet material after it collides with a dense intergalactic medium, or the expansion of a jet-inflated cocoon along the minor axis of an elliptical galaxy (e.g., Leahy and Williams, 1984;Capetti et al, 2002;Kraft et al, 2005;Hodges-Kluck et al, 2010;Hodges-Kluck and Reynolds, 2011;Rossi et al, 2017;Joshi et al, 2019;Cotton et al, 2020).…”
Section: Post-merger Signatures Of Agn Jetsmentioning
confidence: 99%